Commuting spillover: A systematic review and agenda for research. (1st July 2020) - Calderwood, Charles; Mitropoulos, Tanya
Summary: Commuting is a central activity of life that cuts across industries and occupations. Because a large majority of employees commute to work, organizational scholars have long been interested in the relevance of commuting to organizational life. This interest forms the foundation of a research tradition to understand commuting spillover, which reflects interrelationships between commuting and work experiences. Unfortunately, commuting spillover investigations have historically been fractured across publications in the management, psychology, transportation, and ergonomics communities, impeding understanding of the nature and implications of commuting spillover for organizational stakeholders. We conduct a systematic review to identify what is known and unknown about commuting spillover, attending to both between‐ and within‐person approaches to studying this process. This effort yields five major conclusions emerging from the commuting spillover literature, as well as the identification of two frequently investigated topics that have yielded few clear findings within this research base. This knowledge synthesis is used to develop an agenda for the next wave of commuting spillover research that aims to extend this research base while resolving inconsistencies observed in past research. We conclude with calls for methodological advancement and theory development on the commuting spillover topic.